Моніторинг вертикальних зміщень техногенно-навантажених територій геодезичними методами - Петров, Сергій Леонідович (Національний університет "Львівська політехніка", 2019)
Дисертація присвячена дослідженням вертикальних зміщень техногенно-навантажених територій геодезичними методами з врахуванням геодинамічних процесів різного характеру впливу. Проведена класифікація геодезичних методів визначення вертикальних зміщень. Встановлено, що основним недоліком цих методів є дискретність одержуваної інформації. На основі проведеної класифікації цифрових інклінометрів зроблені висновки про подальші напрямки використання в автоматизованих системах моніторингу техногенно-навантажених територій. З метою врахуванням геодинамічних процесів різного характеру впливу розроблено методику опрацювання ГНСС – вимірів на кінематичних геодезичних мережах з врахуванням коефіцієнтів кінематики геодезичних пунктів. Запропонована методика апробована на опорній мережі системи автоматизованого геодезичного моніторингу інженерних споруд Канівської ГЕС. Використання цієї методики опрацювання ГНСС – вимірів без прив’язки до перманентних станцій мережі ITRF, дозволяє ефективно вирішувати задачі з врахування впливу геодинамічних явищ локального характеру на досліджувану територію. На прикладі опорної висотної мережі Рівненської АЕС за даними повторних висотних вимірів проведено групування реперів за кінематичними характеристиками та реалізована методика районування території геодинамічного полігону. Для підтвердження можливості використання геотехнічних методів у поєднанні з геодезичними методами в автоматизованих системах моніторингу розроблена методика сумісного опрацювання результатів геометричного нівелювання та вимірів інклінометрами. Ця експериментально перевірена методика доводить, що нахиломірні виміри можуть бути використані в комплексних автоматизованих системах моніторингу техногенно-навантажених територій, для визначення фонових (у межах жорсткої моделі) нахилів земної поверхні поряд з високоточним геометричним, гідростатичним чи гідродинамічним нівелюванням, які визначають аномальні (деформаційні) зміни земної поверхні. Для вивчення та прогнозування руйнівних процесів на території у межах гірничого відводу шахтних полів рудника № 2 Стебницького калійного родовища створена система автоматизованого моніторингу, яка включає дві нахиломірні станції. Вона дозволяє в режимі реального часу одержувати інформацію про величину та швидкість зміни максимального кута нахилу території та його азимут. Ці результати дозволили розробити методику визначення місць імовірних підземних обвалів. Диссертация посвящена исследованию вертикальных смещений техногенно-нагруженных территорий геодезическими методами с учетом геодинамических процессов различного характера влияния. Проведена классификация геодезических методов определения вертикальных смещений. Установлено, что основным недостатком этих методов является дискретность получаемой информации. На основе проведенной классификации цифровых инклинометров сделаны выводы о дальнейших направлениях использования в автоматизированных системах мониторинга техногенно-нагруженных территорий. С целью учета геодинамических процессов различного характера влияния разработана методика обработки ГНСС – измерений на кинематических геодезических сетях с учетом коэффициентов кинематики геодезических пунктов. Предложенная методика апробирована на опорной сети системы автоматизированного геодезического мониторинга инженерных сооружений Каневской ГЭС. Использование методики обработки ГНСС – измерений без привязки к перманентным станциям сети ITRF позволяет эффективно решать задачи по учету влияния геодинамических явлений локального характера на исследуемую территорию. На примере опорной высотной сети Ровенской АЭС по данным повторных высотных измерений проведено группирование реперов по кинематическим характеристикам и реализована методика районирования территории техногенного геодинамического полигона. Для подтверждения возможности использования геотехнических методов в сочетании с геодезическими методами в автоматизированных системах мониторинга разработана методика совместной обработки результатов геометрического нивелирования и измерений инклинометрами. Эта экспериментально проверенная методика показывает, что наклономерные измерения могут быть использованы в комплексных автоматизированных системах мониторинга техногенно-нагруженных территорий для определения фоновых (в пределах жесткой модели) наклонов земной поверхности наряду с высокоточным геометрическим, гидростатическим или гидродинамическим нивелированием, которые определяют аномальные (деформационные) изменения земной поверхности. Для изучения и прогнозирования разрушительных процессов на территории в пределах горного отвода шахтных полей рудника № 2 Стебницкого калийного месторождения создана система автоматизированного мониторинга, которая состоит из двух наклономерных станций. Она позволяет в режиме реального времени получать информацию о величине и скорости изменения максимального угла наклона территории и его азимут. Эти результаты позволили разработать методику определения мест возможных подземных обвалов. The dissertation is devoted to research of vertical displacements of technogenicloaded territories by geodetic methods taking into account geodynamic processes with different character of the influence. The classification of geodetic methods for determining vertical displacements is carried out. It is established that the main disadvantage of these methods is the discreteness and stippling of the received information. On the basis of implemented classification of digital inclinometers, conclusions about the further directions of use in automated monitoring systems of technogenic-loaded territories were made. In order to consider geodynamic processes with different nature of influence, there was developed the method of processing of GNSS measurements on kinematic geodetic networks with the consideration of kinematics coefficients of geodesic points. The proposed method was tested on the reference network of the system of automated geodetic monitoring of engineering structures of Kaniv HPP. The application of the methodology of processing of GNSS measurement without reference to the permanent stations of the ITRF network allows us to effectively solve problems with considering the influence of geodynamic phenomena of local character on the investigated territory. On the example of the reference high-altitude network of Rivne NPP, the method of mathematical zoning of the territory of technogenic geodynamic landfills according to the data of repeated altitudinal measurements was implemented. On this base the bench mark grouping was performed according to the kinematic characteristics and zoning of the object's territory. The method for joint processing of results of geometric leveling and measurements by inclinometers was developed for confirmation of the possibility of using geotechnical methods in conjunction with geodetic methods in automated monitoring systems. This technique was experimentally tested, the results of the experiment proved that the tilt measurements can be used in complex automated monitoring systems of technogenic-loaded territories, for determination of the background (within the rigid model) tilts of the earth's surface, along with high-precision geometric, hydrostatic or hydrodynamic leveling, which determine abnormal (deformational) changes of the earth's surface. For the study and forecasting of destructive processes on the territory within the mining fields of the mine №.2 of Stebnyk potassium deposit, the system of automated monitoring has been created. It consists of two tilt-shaped stations and allows to receive real-time information about the magnitude and rate of change in the maximum angle of the The dissertation is devoted to research of vertical displacements of technogenicloaded territories by geodetic methods taking into account geodynamic processes with different character of the influence. The classification of geodetic methods for determining vertical displacements is carried out. It is established that the main disadvantage of these methods is the discreteness and stippling of the received information. On the basis of implemented classification of digital inclinometers, conclusions about the further directions of use in automated monitoring systems of technogenic-loaded territories were made. In order to consider geodynamic processes with different nature of influence, there was developed the method of processing of GNSS measurements on kinematic geodetic networks with the consideration of kinematics coefficients of geodesic points. The proposed method was tested on the reference network of the system of automated geodetic monitoring of engineering structures of Kaniv HPP. The application of the methodology of processing of GNSS measurement without reference to the permanent stations of the ITRF network allows us to effectively solve problems with considering the influence of geodynamic phenomena of local character on the investigated territory. On the example of the reference high-altitude network of Rivne NPP, the method of mathematical zoning of the territory of technogenic geodynamic landfills according to the data of repeated altitudinal measurements was implemented. On this base the bench mark grouping was performed according to the kinematic characteristics and zoning of the object's territory. The method for joint processing of results of geometric leveling and measurements by inclinometers was developed for confirmation of the possibility of using geotechnical methods in conjunction with geodetic methods in automated monitoring systems. This technique was experimentally tested, the results of the experiment proved that the tilt measurements can be used in complex automated monitoring systems of technogenic-loaded territories, for determination of the background (within the rigid model) tilts of the earth's surface, along with high-precision geometric, hydrostatic or hydrodynamic leveling, which determine abnormal (deformational) changes of the earth's surface. For the study and forecasting of destructive processes on the territory within the mining fields of the mine №.2 of Stebnyk potassium deposit, the system of automated monitoring has been created. It consists of two tilt-shaped stations and allows to receive real-time information about the magnitude and rate of change in the maximum angle of the terrain and its azimuth. These results allowed to develop a methodology for determining the locations of probable underground cave-in.
Мониторинг вертикальных смещений техногенно-нагруженных территорий геодезическими методами
Monitoring of vertical displacement of technogenic-loaded territories by geodetic methods
Keywords: техногенно-навантажені території; коефіцієнт кінематики геодезичних пунктів; кінематичні характеристики; районування території; цифрові інклінометри; нахиломірні виміри; кут нахилу території; імовірні підземні обвали; техногенно-нагруженные территории; коэффициент кинематики геодезических пунктов; кинематические характеристики; районирование территории; цифровые инклинометры; наклономерные измерения; угол наклона территории; возможные подземные обвалы; technogenic-loaded territories; coefficient of kinematics of geodetic points; kinematic characteristics; zoning of territory; digital inclinometers; tilting measures; tilt angle of the territory; probable underground cave-in; 528.48